Review on the Performance of Different Types of Filter in the Presence of Various Noises - Sarker, Orvila; Akter, Sheuly; Mishu, Afrina Akter (Engineering International, 2016)
An efficient filter must have the quality of removing noise at the same time preserving the information. On the other hand, noise contaminates in the field of signal processing and communication due to various unwanted nonlinear effects. So study of the characteristics of different types of noise is necessary. Also, how various types of filters response to these noises are also important? In this paper, we have studied the characteristics of four types of noise namely Salt & pepper noise, Gaussian noise, Speckle noise and Poisson noise and analyzed the performance of four basic types of filters such as Mean filter, Median filter, Wiener filter and Gaussian filter to suppress the noises mentioned previously.